Mechanics applied to skeletal ontogeny and phylogeny - Prendergast, Patrick John (Springer, 2002)
The musculo-skeletal system serves the mechanical function of creating motion and transmitting loads. It is made up mainly of four components: bone, cartilage, muscle and fibrous connective tissue. These have evolved over millions of years into the complex and diverse shapes of the animal skeleton. The skeleton, however, is not built to a static plan: it can adapt to mechanical forces during growth, it can remodel if the forces change, and it can regenerate if it is damaged. In this paper, the regulation of skeletal construction by mechanical forces is analyzed from both ontogenetic and phylogenetic standpoints. In the first part, models of biomechanical processes that act during skeletal ontogenesis ? tissue differentiation and bone remodeling ? are presented and, in the second, the evolution of the middle ear is used as an example of biomechanical change in skeletal phylogenesis. Because the constitutive laws for skeletal tissues are relatively well understood, and because the skeleton is preserved in the fossil record, application of mechanics to skeletal evolution seems to present a good opportunity to explore the relationships governing ontogenetic adaptations and phylogenetic change.
PUBLISHED
Keywords: Biomechanics - Mechanobiology - Remodeling - Ontogenesis - Vertebrates - Optimization - Developmental mechanics - Palaeobiology